Innovations and Practices in Ornamental Horticulture: Integrating Landscape and Garden Design for Sustainable Aesthetics - Aayush Yadav (International Journal of Trends in Horticulture, 2025)
Ornamental horticulture is a specialized branch of horticultural science focusing on the cultivation, management, and utilization of plants for decorative and environmental purposes. With growing urbanization and lifestyle shifts, the importance of aesthetically pleasing and ecologically sustainable green spaces has significantly increased. Landscape design and garden design, both integral components of ornamental horticulture, contribute not only to the beautification of spaces but also to environmental conservation, mental well-being, and biodiversity enhancement. Landscape design integrates scientific, artistic, and ecological principles to create functional and visually appealing outdoor environments, whereas garden design emphasizes smaller, personalized spaces tailored for recreation, cultural identity, and personal satisfaction. This review discusses the evolution of ornamental horticulture and the contemporary trends in landscape and garden design. It explores plant selection, design principles, cultural symbolism, and technological innovations such as computer-aided design (CAD), vertical gardens, and smart irrigation systems. Special emphasis is placed on the role of native plant species, sustainable resource management, and climate-responsive designs in addressing environmental challenges. Literature evidence shows that ornamental landscapes play a key role in reducing urban heat, improving air quality, and enhancing urban biodiversity. Furthermore, the review highlights the psychological benefits of green spaces, particularly their role in stress reduction, productivity enhancement, and social interaction. Despite its global importance, ornamental horticulture faces challenges including limited awareness, high maintenance costs, and climate change-related stresses on plant growth and survival. Future directions suggest integrating ecological horticulture practices with modern landscape architecture and promoting community participation in garden design. By bridging art, science, and sustainability, ornamental horticulture holds promise for shaping healthier, greener, and more livable human environments.
Keywords: Garden design; Landscape design; Ornamental horticulture; Sustainable aesthetics; Urban green spaces